2005
DOI: 10.1002/ajh.20315
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic pneumonitis as the manifestation of acute graft‐versus‐host disease of the lung

Abstract: Acute graft-versus-host disease is a common complication after allogeneic stem cell transplantation. It normally affects the skin, liver, and gut. We report a 54-year-old male who developed shortness of breath, cough, and bilateral pulmonary infiltrates in which the workup failed to demonstrate an infectious etiology 165 days post-HLA-matched allogeneic peripheral blood stem cell transplant. Eighteen days before, his tacrolimus had been tapered and it was subtherapeutic on admission. A transbronchial biopsy sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…In a study of HCT recipients with bloodstream infections, postengraftment events were associated with worse outcomes, including death (62). "Late onset" noninfectious PCs, which may be subjected to diagnostic inaccuracy (63), have been associated with acute and chronic GVHD (35,64,65) and mortality (66). Many subjects in our study had multiple PCs, suggesting susceptibility to recurrent lung injury, incomplete resolution, and/or misdiagnosis and treatment of a previous PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of HCT recipients with bloodstream infections, postengraftment events were associated with worse outcomes, including death (62). "Late onset" noninfectious PCs, which may be subjected to diagnostic inaccuracy (63), have been associated with acute and chronic GVHD (35,64,65) and mortality (66). Many subjects in our study had multiple PCs, suggesting susceptibility to recurrent lung injury, incomplete resolution, and/or misdiagnosis and treatment of a previous PC.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-four of 112 (83.8%) PCs were first diagnosed by chest CT, and 71.4% (80 of 112) of radiographic findings were described as multifocal (35) or diffuse (20). Thirty-three PCs (29.2%) occurred during the first 30 days, and 86 (76.8%) occurred by the end of the first post-transplantation year.…”
Section: Pulmonary Complications Mortality and Other Clinical Outcomesmentioning
confidence: 99%
“…Cooke et al [9] first found that lung injury was encountered in the process of aGVHD. Many animal experiments of aGVHD also confirmed that early non-infectious diffused lung injury was associated with aGVHD [1,10−12] and this was also supported by clinical studies [13,14] , but whether the lung is one of the target organs of aGVHD remains undetermined [1,2,10,15] .…”
Section: Discussionmentioning
confidence: 68%
“…LIP is a rare late-onset, non-infectious pulmonary complication of chronic GVHD 1012. LIP is better described in the non-transplant setting where it is often associated with adult autoimmune or paediatric immunodeficiency disorders 10.…”
Section: Discussionmentioning
confidence: 99%